Microwave Moisture Measurement of Cotton Fiber Moisture Content in the Laboratory. Issue 3 (May 2017) - Rodgers, James; Zumba, Jimmy; Delhom, Christopher
The moisture content of cotton fiber is an important fiber property, but is often measured by a laborious, time-consuming, laboratory oven-drying method. The ability of a laboratory microwave moisture measurement instrument to perform rapid, precise, and accurate fiber moisture measurements was studied. The microwave instrument was calibrated versus two significantly different oven-drying methods. The agreement between the two oven-drying methods was very good, with low residuals observed. The precision of the microwave moisture content measurements was very high, approaching 0.1% moisture. The impact of sample fiber weight was minor, and instrument stability and long-term repeatability were excellent. Microwave cotton fiber moisture content measurement was shown to be viable and applicable for quality control use.